Kilka uwag o relacjach społecznych panujących w domach pomocy społecznej – z raportu dotyczącego badań kultury organizacyjnej - Niedbalski, Jakub (Życie z niepełnosprawnością w świecie VUCA, 2022)
This paper aims to determine some dominating features of one of two theoretical models that describe an organizational cultural of a social welfare home, namely bureaucratic – repressive and individualist – autonomous. The nature of the interaction between the community of residents and staff and the relationships within each of these groups was studied to determine which of these models most accurately reflects the characteristics of social welfare facilities, and this course of interaction directions was called the “four fronts of interaction.” To achieve the study objective and decide which model dominates in conditions of social welfare homes we employed participant observation and unstructured interviews, and this allowed us to gather the necessary empirical material.